Implementasi Manajemen Evaluasi dalam Kurikulum Merdeka di SMK Muhammadiyah Delanggu - Muhammad Hafidz Al Jauzy; Hendi Perdana; Ilham Ramdani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study describes the implementation of Independent curriculum and analyze its challenges at SMK Muhammadiyah Delanggu. The author uses qualitative approach and field research as his method. Data collection is done by direct observation, interviews, and documentation. The results of this study indicate that (1) The implementation of the independent curriculum at SMK Muhammadiyah is almost fully implemented, but it still leaves grade 12 which still uses the 2013 curriculum model. (2) The role of curriculum management is crucial in determining the direction of the curriculum in schools, (3) Challenges in implementing the independent curriculum at SMK Muhammadiyah Delanggu, namely teachers who are not fully familiar with the Merdeka curriculum and limited tools and materials that make project-based learning hampered. (4) The efforts made by curriculum management in overcoming these obstacles are trying to improve the quality of teachers by increasing workshops and trainings and maximizing the tools and materials that are already available.